Pengembangan Aplikasi Puskesmas Untuk Pasien Umum Menggunakan Pendekatan Web Semantik (Studi Kasus UPT Puskesmas Bareng Kota Malang) - Gerry Giovanni Benson; Bayu Priyambadha; Djoko Purnomo (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
The Community Health Center or Health Center is one of the means which cooperate with the government in the development of the health sector. Service in Bareng Health Center located in the Bareng, Klojen disctrict, Malang City is divided into two types of patients that are the type of patient BPJS and the type of general patient. This causes a variety of problems such as difficulty in finding patient files stored in archives, patient file which can be lost or damaged, duplicated, and human errors. Of these problems, we need a development of an information system applications that can handle data storage and processing automatically so as to facilitate the performance of Health Center. This research was conducted using Waterfall System Development Life Cycle method and using semantic web approach. The system was built based website using PHP technology, Apache Fuseki Jena, MySQL, and Javascript. This study uses a compatibility testing that showed good results in the Mozilla Firefox and Google Chrome browser and the white-box testing showed results of 100% valid from 9 test cases and black-box testing showed a 100% valid from 37 test cases and recall testing of semantics showed 100% of 5 test cases, while the precision testing showed 90% of 5 test cases.